The Boss' Healthy Buddies Nutrition Resource Is Effective for Elementary School Students - David W. Pittman; Ida R. Bland; Isai D. Cabrera; Kassie E. Franck; Emily L. Perkins; Nicole A. Schmidt; Heather N. Allen; Savanah R. Atkins; Sharyn B. Pittman (Hindawi Limited, 2018)
Previously we have shown that our Healthy Eating Decisions school-based intervention can influence students' selections of the healthiest foods available in their elementary school cafeterias through positive reinforcement techniques. Although effective, we recognized that students were missing fundamental nutrition knowledge necessary to understand why the Healthy Eating Decisions program identified particular beverages and foods as the healthiest in the cafeteria. Therefore, we developed the Boss' Healthy Buddies nutrition education resource as a freely available curriculum matched with South Carolina education standards and designed for elementary school students from kindergarten through fourth grade. The current study implemented Boss' Healthy Buddies and compared its efficacy to a commercially available nutrition program, CATCH. Elementary school students in Spartanburg, South Carolina, received weekly twenty-minute Boss' Healthy Buddies lessons for eight weeks. Results from preassessment and postassessment surveys were compared with a positive control elementary school using the CATCH program and a negative control school receiving no nutrition education. Results show that Boss' Healthy Buddies was equally effective as the CATCH program in improving the nutrition attitudes regarding healthiest beverages and food selections with the advantage of being freely available and minimizing the impact on classroom instruction time. In order to reduce most effectively the high prevalence of childhood overweight and obesity, it is crucial that children are taught nutrition education to support healthy eating habits at an early age. Both the Healthy Eating Decisions school-based intervention and the Boss' Healthy Buddies nutrition education program are available online for use as free resources to aid in reducing childhood overweight and obesity within elementary schools.